2007
DOI: 10.1158/1078-0432.ccr-06-0774
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Types of Blood Vessels in Clear Cell Renal Cell Carcinoma Have Contrasting Prognostic Implications

Abstract: Purpose: Intratumoral microvascular density (MVD) has been controversial as an indicator of prognosis in clear cell renal cell carcinoma (CCRCC). Classification of the intratumoral blood vessels based on differential expressions of blood vessel markers has not been correlated with patient prognosis in CCRCC. In this study, we aimed to evaluate the association of different categories of blood vessels with the patients'outcomes. Experimental Design: Seventy-eight CCRCC patients who underwent nephrectomy alone we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(102 citation statements)
references
References 41 publications
4
92
0
4
Order By: Relevance
“…These findings suggest that CC-RCC with high MVD and low ECP% may have a more stabilised and mature vasculature than their counterpart. Our finding is concordant with a recent study, which described differentiated and undifferentiated types of blood vessels in CC-RCC (Yao et al, 2007). They found that an increased density of undifferentiated vessels significantly correlated with higher pathological grades and shorter patient survival.…”
Section: Discussionsupporting
confidence: 93%
“…These findings suggest that CC-RCC with high MVD and low ECP% may have a more stabilised and mature vasculature than their counterpart. Our finding is concordant with a recent study, which described differentiated and undifferentiated types of blood vessels in CC-RCC (Yao et al, 2007). They found that an increased density of undifferentiated vessels significantly correlated with higher pathological grades and shorter patient survival.…”
Section: Discussionsupporting
confidence: 93%
“…For example, in tumors such as clear cell renal cell carcinoma, both differentiated and undifferentiated vessels (i.e. vessels made up of cells that have grown to the normal mature stage of development and vessels made up of cells that remain in an immature or ''primitive'' stage) coexist, which could serve as a basis for an alternative classification (Yao et al, 2007). Therefore, it seems to us that the studies aiming at determining a fractal dimension from 2D thin tissue sections of tumor tissues (for example Weyn et al, 2004) must be interpreted with great caution until these methodological issues are resolved.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent study demonstrated that within CCRCC there are at least 2 major categories of blood vessels having contrasting prognostic implications: the undifferentiated vessels (expressing CD31 but not CD34) and the differentiated vessels (expressing both CD31 and CD34). 34 The morphologic characteristics of undifferentiated vessels include no (or a small) lumen, a thicker vessel wall, and smaller size when compared with differentiated vessels. A higher density of undifferentiated vessels is correlated with shorter patient survival, higher grade tumors, and a more advanced primary tumor.…”
Section: Differential Analysis Of Tumor Vasculaturementioning
confidence: 99%